2021
DOI: 10.1002/hrdq.21454
|View full text |Cite
|
Sign up to set email alerts
|

Type A/B personality, work–family, and family–work conflict: The moderating effects of emotional intelligence

Abstract: Many employees experience work-family conflict (WFC) and family-work conflict (FWC), multidimensional states of resource depletion. In this paper, we conceptualize Type A and B personality as resource depletion and resource gain scenarios that have implications for perceptions of WFC and FWC. We draw on conservation of resources (COR) theory to examine the resource loss and gain resulting respectively from Type A and B personality and the resource-generating role of ability-based emotional intelligence (EI) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 99 publications
0
7
0
3
Order By: Relevance
“…For the first time in 1994, Mayer proposed the concept 'emotional intelligence' as the ability to recognize and regulate emotions in one and others (Goleman, 1995) suggested that although cognitive intelligence may provide some individuals with entry into a particular setting, emotional intelligence may serve a vital role in determining how successful they will be after entering the setting. Furthermore, Goleman (1995) in his book Emotional Intelligence divided it into emotional self-awareness (such as separating feelings from actions), managing emotions (such as controlling anger), realizing others' emotions (such as taking the perspective of others; Garavan et al,2022), and handling relationships (such as solving relation problems). Individuals would improve their emotional intelligence because of its influence on strengthening their ability to monitor themselves and their abilities, so they conduct them in a way to make benefits them (Goleman, 1995).…”
Section: Review Of Literaturementioning
confidence: 99%
“…For the first time in 1994, Mayer proposed the concept 'emotional intelligence' as the ability to recognize and regulate emotions in one and others (Goleman, 1995) suggested that although cognitive intelligence may provide some individuals with entry into a particular setting, emotional intelligence may serve a vital role in determining how successful they will be after entering the setting. Furthermore, Goleman (1995) in his book Emotional Intelligence divided it into emotional self-awareness (such as separating feelings from actions), managing emotions (such as controlling anger), realizing others' emotions (such as taking the perspective of others; Garavan et al,2022), and handling relationships (such as solving relation problems). Individuals would improve their emotional intelligence because of its influence on strengthening their ability to monitor themselves and their abilities, so they conduct them in a way to make benefits them (Goleman, 1995).…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the past three decades significant research has been conducted to understand the concept of WFC (Garavan et al, 2021) because of its deeper impact on employees, their families and organizations (Baral and Sampath, 2019). Greenhaus and Beutell (1985) defined WFC as "a type of inter role -conflict in which role demands from one domain (work or family) is incompatible with role demands from another domain" which is further classified into three categories:…”
Section: Work-family Conflictmentioning
confidence: 99%
“…Konflik interpersonal di tempat kerja adalah salah satu sumber yang berhubungan dengan pekerjaan yang paling menonjol dari stres bagi karyawan [7]. Mengingat bahwa sebagian besar pekerjaan membutuhkan beberapa tingkat interaksi dengan orang lain, konflik interpersonal dianggap baik karakteristik yang tak terelakkan [8]. Konflik interpersonal di tempat kerja umumnya mengacu pada perbedaan pendapat di antara individu-individu sebagai akibat dari oposisi yang dirasakan tentang kepentingan atau tujuan masing-masing [9].…”
Section: Pendahuluanunclassified
“…Hubungan positif yang signifikan juga telah ditemukan antara konflik interpersonal di tempat kerja dan perilaku kerja kontraproduktif, termasuk sabotase, agresi, permusuhan dan pencurian, serta ketidakhadiran [12]. Dalam hal kesehatan individu dan kesejahteraan, pengalaman konflik interpersonal adalah terkait dengan depresi [11], kecemasan dan frustrasi [13], kesehatan mental umum [8], dan kelelahan [14].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation